To be a machine : adventures among cyborgs, utopians, hackers, and the futurists solving the modest problem of death - O'Connell, Mark, 1979- (Doubleday, 2017)
"A globe-spanning investigation into the Transhumanist movement, considering the tech billionaires, scientific luminaries, and DIY body-hackers attempting to prolong, improve, and ultimately transcend the limits of human life"--